2015
DOI: 10.1037/abn0000077
|View full text |Cite
|
Sign up to set email alerts
|

Weight suppression in bulimia nervosa: Associations with biology and behavior.

Abstract: Bulimia nervosa (BN) is a serious eating disorder that can persist for years and contribute to medical complications and increased mortality, underscoring the need to better understand factors maintaining this disorder. Higher levels of weight suppression (WS) have been found to predict both the onset and maintenance of BN; however, no studies have examined mechanisms that may account for the effects of WS on BN. We hypothesized that high WS would lead to reduced leptin levels, which may increase risk of binge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
57
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 83 publications
(142 reference statements)
7
57
2
Order By: Relevance
“…This idea is consistent with psychobiological theories of WS and BN and with our previous study finding correlations between WS and leptin and the reinforcing value of food (Bodell & Keel, 2015). Although speculative, it is possible that leptin may mediate associations between WS and DT found in the current study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This idea is consistent with psychobiological theories of WS and BN and with our previous study finding correlations between WS and leptin and the reinforcing value of food (Bodell & Keel, 2015). Although speculative, it is possible that leptin may mediate associations between WS and DT found in the current study.…”
Section: Discussionsupporting
confidence: 93%
“…Several cross-sectional studies have reported significant associations between higher WS and greater frequency of binge eating and purging in individuals with BN (Bodell & Keel, 2015; Butryn, Juarascio, & Lowe, 2011; Lowe, Thomas, Safer, & Buytryn, 2007). Furthermore, longitudinal studies support the role of WS in the maintenance of BN (Butryn, Lowe, Safer, & Agras, 2006; Keel & Heatherton, 2010; Lowe et al, 2011).…”
mentioning
confidence: 99%
“…These tasks require participants to press a keyboard button an increasing number of times to receive food rewards that they are then asked to consume. One adaptation of this task was used to compare how hard adult women with BN worked for chocolate candies (food reinforcers) relative to controls [68]. Participants could earn 10 candies per trial for 10 total trials.…”
Section: Reward Responsivity Valuation and Learningmentioning
confidence: 99%
“…The progressive ratio task version that requires individuals to immediately consume the candies earned [68] may more closely mimic original progressive ratio tasks used to measure food and drug reinforcement in rodent models, and may measure the reinforcing value of continuing to consume food over time after eating has commenced. The version of the task with delayed consumption [69] more closely resembles human drug studies in which participants sample the drug on the study day and earn tokens to self-administer the drug on the days following the experiment [70].…”
Section: Reward Responsivity Valuation and Learningmentioning
confidence: 99%
“…The field of behavioral economics provides methods by which to measure the motivation to engage in behaviors like smoking (Epstein, Bulik, Perkins, Caggiula, & Rodefer, 1991), drug use (Comer et al, 1998), physical activity (Schebendach, Klein, Foltin, Devlin, & Walsh, 2007); (Saelens & Epstein, 1999), and eating (Bodell & Keel, 2015; Epstein & Leddy, 2006; Epstein, Leddy, Temple, & Faith, 2007; Haynos, Hill, & Fruzzetti, 2016; Schebendach, Broft, Foltin, & Walsh, 2013) in a laboratory setting. In general, these laboratory paradigms quantify motivation in terms of the amount of “work” an individual is willing to expend to gain access to a specific a substance or behavior, often referred to as a reinforcer (Hodos, 1961).…”
Section: Introductionmentioning
confidence: 99%